Blood glucose management in the intensive care unit : insulin infusion protocol - Mat Nor, Mohd Basri (Ministry of Heatlh Malaysia, 2012)
Stress hyperglycaemia is associated with poor clinical outcomes in critically ill patients. Factors contributing to hyperglycemia in critical illness include the release of stress hormones, the use of medications, the release of mediators in sepsis and trauma and insulin resistance